Gene ontology improves template selection in comparative protein docking. Issue 3 (27th December 2018) - Hadarovich, Anna; Anishchenko, Ivan; Tuzikov, Alexander V.; Kundrotas, Petras J.; Vakser, Ilya A.
Abstract: Structural characterization of protein‐protein interactions is essential for our ability to study life processes at the molecular level. Computational modeling of protein complexes (protein docking) is important as the source of their structure and as a way to understand the principles of protein interaction. Rapidly evolving comparative docking approaches utilize target/template similarity metrics, which are often based on the protein structure. Although the structural similarity, generally, yields good performance, other characteristics of the interacting proteins (eg, function, biological process, and localization) may improve the prediction quality, especially in the case of weak target/template structural similarity. For the ranking of a pool of models for each target, we tested scoring functions that quantify similarity of Gene Ontology (GO) terms assigned to target and template proteins in three ontology domains—biological process, molecular function, and cellular component (GO‐score). The scoring functions were tested in docking of bound, unbound, and modeled proteins. The results indicate that the combined structural and GO‐terms functions improve the scoring, especially in the twilight zone of structural similarity, typical for protein models of limited accuracy.